2018
DOI: 10.1055/a-0576-1028
|View full text |Cite
|
Sign up to set email alerts
|

Subependymomas – Characteristics of a “Leave me Alone” Lesion

Abstract: · Kammerer S, Mueller-Eschner M, Lauer A et al. Subependymomas - Characteristics of a "Leave me Alone" Lesion. Fortschr Röntgenstr 2018; 190: 955 - 966.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…Though the majority of cases in our study demonstrated enhancement, it is worth noting that most of these tumors exhibited relatively mild to moderate enhancement. This is generally consistent with what has been previously described in multiple retrospective case series with regards to intracranial subependymoma [ 8 , 10 12 , 16 – 18 , 21 , 22 ]. It is worth noting that none of our lesions demonstrated complete enhancement, and only one demonstrated avid enhancement.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Though the majority of cases in our study demonstrated enhancement, it is worth noting that most of these tumors exhibited relatively mild to moderate enhancement. This is generally consistent with what has been previously described in multiple retrospective case series with regards to intracranial subependymoma [ 8 , 10 12 , 16 – 18 , 21 , 22 ]. It is worth noting that none of our lesions demonstrated complete enhancement, and only one demonstrated avid enhancement.…”
Section: Discussionsupporting
confidence: 92%
“…The most common symptoms noted in our study included headache and dizziness, which are consistent with the literature [10,14,22,29]. Obstructive hydrocephalus was also observed in three of our patients before surgery, which was noted in the literature to be a particular sequelae of fourth ventricle subependymoma [10,17,18]. None of the cases in our study experienced tumor recurrence, consistent with the literature regarding the clinical management and cellular growth of intracranial subependymoma [8,9,[12][13][14][15]30].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations